Wheat and rice seed coating material and coating process
By coating wheat and rice seeds with micron-sized iron powder, nano-calcium phosphate, nano-magnesium hydroxide, and binders to form a uniform and dense coating layer, the problem of precise passivation of heavy metals in soil is solved. This achieves efficient adsorption and fixation of heavy metal ions in seeds and soil, promotes seedling growth, reduces costs, and minimizes soil disturbance.
Patent Information
- Application Number
- CN202610196717.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-11
- Publication Date
- 2026-03-20
AI Technical Summary
Existing barley and rice coating agents mainly focus on pest and disease control and nutrient supply, lacking technology for the passivation of heavy metals in soil. Furthermore, traditional passivating agent application methods suffer from large dosages, uneven distribution, and poor compatibility with crop roots, making it difficult to meet the precision needs of in-situ soil remediation in farmland.
Wheat and rice seed coating materials, including micron-sized iron powder, nano-sized calcium phosphate, nano-sized magnesium hydroxide, and binders, are used to form a uniform and dense coating layer on the outside of the seeds through super-acceleration coating technology, thereby achieving efficient adsorption and fixation of heavy metal ions.
It achieves integrated control of heavy metal ions in seeds and soil, improves seed compressive strength, promotes seedling growth, reduces costs, minimizes soil disturbance, and enables precise remediation and treatment of heavy metal contaminated soil.
Smart Images

Figure CN121698696A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of seed coating materials technology, specifically to a coating material and coating process for wheat and rice seeds. Background Technology
[0002] Currently, farmland heavy metal pollution remediation technologies are mainly divided into three categories: ① Physical remediation (such as soil replacement and electrostatic remediation) has significant effects but is costly and easily causes damage to soil structure; ② Chemical remediation (such as the application of lime and phosphate) can quickly fix heavy metals, but often leads to soil compaction and nutrient imbalance, and poses a risk of secondary pollution; ③ Bioremediation (such as planting hyperaccumulating plants and microbial remediation) is environmentally friendly, but has a long remediation cycle and is significantly limited by geographical conditions.
[0003] Seed coating technology is one of the key technologies in modern agriculture. By coating the outer surface of seeds with a layer of functional material, it can improve seed uniformity, enhance stress resistance, carry pesticides and fertilizers, and facilitate precision mechanized sowing. Existing technologies (such as CN120959247A) mainly focus on improving the coating processing performance and agronomic traits of barley and rice seeds through the compounding of specific fillers (such as talc and bentonite).
[0004] Therefore, existing barley and rice seed coating agents primarily focus on pest and disease control and nutrient supply, lacking technology for the passivation of heavy metals in soil. Furthermore, traditional passivating agent application methods suffer from problems such as large dosages, uneven distribution, and poor compatibility with crop root systems, failing to meet the precise needs of in-situ soil remediation in farmland. There is an urgent need to develop a seed coating material and coating process for wheat and rice that combines seed germination promotion with precise passivation of heavy metals in soil. Summary of the Invention
[0005] To address the aforementioned problems, the present invention aims to provide a coating material and coating process for wheat and rice seeds.
[0006] To achieve the above objectives, the present invention provides a seed coating material for wheat and rice, comprising micron-sized iron powder, nano-sized calcium phosphate, nano-sized magnesium hydroxide, and a binder; wherein the amounts of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide are 10%–20%, 2%–10%, and 3%–10% of the total seed weight, respectively. The adhesive is at least one of polyvinyl alcohol colloidal solution, carboxymethyl cellulose colloidal solution, and hydroxypropyl methyl cellulose colloidal solution.
[0007] The mass ratio of the binder to the mass of micronized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide is 1:20 to 1:50.
[0008] Furthermore, the amounts of the micronized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide added account for 10%, 3%, and 3% of the total weight of the seeds, respectively; the binder is a polyvinyl alcohol colloidal solution with a mass fraction of 8.0%, and the mass ratio of the polyvinyl alcohol colloidal solution to the combined mass of the micronized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide is 1:32.
[0009] Furthermore, the amounts of the micronized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide added account for 12%, 3%, and 3% of the total weight of the seeds, respectively; the binder is a polyvinyl alcohol colloidal solution with a mass fraction of 8.0%, and the mass ratio of the polyvinyl alcohol colloidal solution to the combined mass of the micronized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide is 1:31.
[0010] Furthermore, the mass ratio of the micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is (1-10):(1-6):(1-5).
[0011] Furthermore, the mass ratio of the micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is 10:3:3.
[0012] Furthermore, the mass ratio of the micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is 4:1:1.
[0013] Further, the mass fraction of the polyvinyl alcohol colloidal solution is 4.0% to 10.0%; the mass fraction of the carboxymethyl cellulose colloidal solution is 1.0% to 5.0%; and the mass fraction of the hydroxypropyl methyl cellulose colloidal solution is 8.0% to 15.0%.
[0014] Secondly, this invention provides a coating process for wheat and rice seed coating materials, specifically including the following steps: Step 1, Seed pretreatment: Select plump wheat or rice seeds free from pests and diseases, remove shriveled, impurities and damaged seeds by winnowing and screening, and dry them at room temperature under ventilation for later use. Step 2, Super-acceleration Coating: Weigh out micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide according to the above raw material ratio, and prepare a binder. First, add wheat or rice seeds and micron-sized iron powder to the super-acceleration coating device and mix them. Then add the binder. Set the operating conditions of the super-acceleration coating device to an acceleration of 30g-80g, a frequency of 55Hz-75Hz, and a running time of 5min-10min. Then add nano-calcium phosphate and nano-magnesium hydroxide to the super-acceleration coating device. Similarly, set the operating conditions of the super-acceleration coating device to an acceleration of 30g-80g and a frequency of 55Hz-75Hz, and continue running for 5min-10min. Step 3, air drying: Dry the wheat and rice coated seeds under natural ventilation conditions.
[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention integrates seed coating technology with soil heavy metal ion adsorption and mineralization for the first time. Wheat and rice seeds are loaded with coating materials. The coating materials can not only protect the seeds, but their functional materials (micron iron powder, nano calcium phosphate and nano magnesium hydroxide) can also be slowly released in the soil to efficiently adsorb and fix lead, cadmium and arsenic heavy metal ions, thus achieving integrated prevention and control from "seed" to "rhizosphere".
[0016] (2) Seed performance is comprehensively improved
[0017] Excellent mechanical properties: This invention uses micron-sized iron powder, nano-sized calcium phosphate and nano-sized magnesium hydroxide, and uses a binder to coat the seeds in multiple layers, making the outer coating layer of the seeds uniform and dense, and improving the compressive strength of the seeds, so that they meet the requirements of high-speed mechanized sowing, and significantly reducing the rate of missed sowing and re-sowing.
[0018] Good agronomic traits: The coating material of this invention uses micron-sized iron powder, nano-calcium phosphate and nano-magnesium hydroxide. The Fe, P and Mg elements contained therein are slowly released, which can promote the growth of seedling roots and above-ground parts. The germination rate and seedling vigor are better than those of uncoated seeds.
[0019] (3) In the coating material of the present invention, the micron iron powder, nano calcium phosphate and nano magnesium hydroxide materials have high adsorption capacity for heavy metal ions such as As, Pb and Cd, respectively, covering the most common and most harmful heavy metal ions in polluted farmland.
[0020] (4) Compared with the traditional method of applying passivating agents across the entire field, this invention achieves precise targeted delivery of functional materials through seed coating, which can reduce the dosage, lower costs, and minimize disturbance to the soil environment, avoiding the problem of unstable remediation effects caused by uneven distribution of traditional passivating agents. After years of use, it can indirectly achieve the remediation and treatment of soil contaminated with heavy metals.
[0021] (5) The coating process of the present invention is simple and easy to implement, and is suitable for large-scale promotion and application. It not only improves the bonding strength between the coating material and the seed, but also ensures the uniformity of the coating layer, thus providing a reliable guarantee for subsequent mechanized sowing. At the same time, the process causes little damage to the seeds and can effectively maintain the original viability of the seeds, laying the foundation for high and stable crop yields.
[0022] (6) The functional materials selected in this invention are widely available, inexpensive, and environmentally friendly, and will not cause secondary pollution to the soil ecosystem. Micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide are all common inorganic materials with mature preparation techniques and easy access, which provides convenient conditions for the practical application of this invention. Attached Figure Description
[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 These are comparative images of wheat coated seeds obtained in Examples 1, 1, 3, 4 and 5 of this invention.
[0025] Figure 2 These are comparative images of rice coated seeds obtained in Examples 4, 2, 6, 7 and 8 of this invention.
[0026] Figure 3 This is a comparison chart of wheat seed sprout length tests on day 4 in Example 1 and Comparative Example 1 of the present invention, showing the development of wheat seedlings.
[0027] Figure 4 This is a comparison chart of wheat seed root length tests on day 4 in Example 1 and Comparative Example 1 of the present invention, showing the development of wheat seedlings.
[0028] Figure 5 This is a comparison chart of wheat seed sprout length tests on day 8 in Example 1 and Comparative Example 1 of the present invention, showing the development of wheat seedlings.
[0029] Figure 6 This is a comparison chart of wheat seed root length tests on day 8 in Example 1 and Comparative Example 1 of the present invention, showing the development of wheat seedlings.
[0030] Figure 7 This is a comparison chart of the rice seed sprout length test on day 5 in Example 4 and Comparative Example 2 of the present invention, showing the development of rice seedlings.
[0031] Figure 8 This is a comparison chart of the root length test of rice seeds on day 5 in Example 4 and Comparative Example 2 of the present invention, showing the development of rice seedlings.
[0032] Figure 9 This is a comparison chart of the rice seed sprout length test on day 14 in Example 4 and Comparative Example 2 of the present invention, showing the development of rice seedlings.
[0033] Figure 10 This is a comparison chart of the root length test of rice seeds on day 14 in Example 4 and Comparative Example 2 of the present invention, showing the development of rice seedlings.
[0034] Figure 11 The graph shows the isothermal adsorption curves of lead, cadmium, and arsenic heavy metal ions by micron-sized iron powder; among them, Figure 11 (a) Pb² is the effect of micron-sized iron powder on Pb² + Isothermal adsorption curves; Figure 11 (b) is the effect of micron-sized iron powder on Cd² + Isothermal adsorption curves; Figure 11 (c) represents the effect of micron-sized iron powder on AsO4³ - The isothermal adsorption curve.
[0035] Figure 12 The image shows the isothermal adsorption curves of lead, cadmium, and arsenic heavy metal ions on nano-calcium phosphate; among them, Figure 12 (a) is the effect of nano-calcium phosphate on Pb² + Isothermal adsorption curves; Figure 12 (b) is the effect of nano-calcium phosphate on Cd² + Isothermal adsorption curves; Figure 12 (c) is nano-calcium phosphate on AsO4³ - The isothermal adsorption curve.
[0036] Figure 13 The image shows the isothermal adsorption curves of lead, cadmium, and arsenic heavy metal ions on nano-magnesium hydroxide; among them, Figure 13 (a) Nano-sized magnesium hydroxide on Pb² + Isothermal adsorption curves; Figure 13 (b) is the effect of nano-magnesium hydroxide on Cd²⁻. + Isothermal adsorption curves; Figure 13 (c) is nano-magnesium hydroxide on AsO4³ - The isothermal adsorption curve. Detailed Implementation
[0037] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0038] The present invention will now be described in detail with reference to the accompanying drawings.
[0039] Reagent sources: Micron-sized iron powder and nano-calcium phosphate were obtained from Aladdin Reagents; nano-magnesium hydroxide was obtained from Shanghai Yingcheng New Materials Co., Ltd.; polyvinyl alcohol, carboxymethyl cellulose, and hydroxypropyl methyl cellulose were also obtained from Aladdin Reagents.
[0040] In this invention, the adhesive is prepared by: (1) Polyvinyl alcohol colloidal solution with a mass fraction of 4.0% to 10.0%: Take 4g to 10g of polyvinyl alcohol with a low degree of alcoholysis of 87% to 89% and add it to 100ml of deionized water. Heat the water bath to 90℃ and stir magnetically for 2h to obtain a polyvinyl alcohol colloidal solution with a mass fraction of 4.0% to 10.0%.
[0041] (2) Carboxymethyl cellulose colloidal solution with a mass fraction of 1.0% to 5.0%: Take 1g to 5g of hydroxymethyl cellulose and slowly add it to 100ml of deionized water. Stir magnetically for 3 hours to obtain a carboxymethyl cellulose colloidal solution with a mass fraction of 1.0% to 5.0%.
[0042] (3) A hydroxypropyl methylcellulose colloidal solution with a mass fraction of 8.0%–15.0%: Add 8g to 15g of hydroxypropyl methylcellulose to 100ml of deionized water at 80℃, disperse by magnetic stirring, stop heating, cool to room temperature and continue stirring for 3 hours until transparent, resulting in a hydroxypropyl methylcellulose colloidal solution with a mass fraction of 8.0% to 15.0%.
[0043] Example 1
[0044] Wheat seeds were selected for this embodiment.
[0045] A seed coating material for wheat and rice includes micron-sized iron powder, nano-sized calcium phosphate, nano-sized magnesium hydroxide, and a binder; The mass ratio of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is 10:3:3.
[0046] The amounts of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide added account for 10%, 3%, and 3% of the total seed weight, respectively.
[0047] The binder is a polyvinyl alcohol colloidal solution with a mass fraction of 8.0%, and the mass ratio of the polyvinyl alcohol colloidal solution to the combined mass of micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide is 1:32.
[0048] The coating process for the above-mentioned coating materials is as follows: Step 1, Seed pretreatment: Select plump wheat seeds free from pests and diseases, remove shriveled, impurities and damaged seeds by winnowing and screening, and dry them in a well-ventilated environment at room temperature for later use. Step 2, Super-acceleration Coating: Weigh out micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide according to the above raw material ratio, and prepare a binder. First, add wheat seeds and micron-sized iron powder to the super-acceleration coating device and mix them. Then add the binder. Set the operating conditions of the super-acceleration coating device to an acceleration of 60g, a frequency of 60Hz, and a running time of 5min to 10min. Then add nano-calcium phosphate and nano-magnesium hydroxide to the super-acceleration coating device. Similarly, set the operating conditions of the super-acceleration coating device to an acceleration of 60g and a frequency of 60Hz, and continue to run for 5min to 10min. Step 3, air drying: Dry the wheat coated seeds under natural ventilation conditions.
[0049] Example 1 is the best embodiment of wheat seed coating material.
[0050] Example 2
[0051] Wheat seeds were selected for this embodiment.
[0052] A seed coating material for wheat and rice includes micron-sized iron powder, nano-sized calcium phosphate, nano-sized magnesium hydroxide, and a binder; The mass ratio of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is 2:1:2.
[0053] The amounts of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide added account for 10%, 5%, and 10% of the total seed weight, respectively.
[0054] The binder is a 10.0% polyvinyl alcohol colloidal solution, and the mass ratio of the polyvinyl alcohol colloidal solution to the combined mass of micronized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide is 1:50.
[0055] The coating process of the above-mentioned coating material differs from that of Example 1 in that: Step 2, Super-acceleration Coating: Weigh out micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide according to the above raw material ratio, and prepare a binder. First, add wheat seeds and micron-sized iron powder to the super-acceleration coating device and mix them. Then add the binder. Set the operating conditions of the super-acceleration coating device to an acceleration of 30g, a frequency of 55Hz, and a running time of 5min. Then add nano-calcium phosphate and nano-magnesium hydroxide to the super-acceleration coating device. Similarly, set the operating conditions of the super-acceleration coating device to an acceleration of 30g and a frequency of 55Hz, and continue to run for 5min.
[0056] Example 3
[0057] Wheat seeds were selected for this embodiment.
[0058] A seed coating material for wheat and rice includes micron-sized iron powder, nano-sized calcium phosphate, nano-sized magnesium hydroxide, and a binder; the mass ratio of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is 1:1:1.
[0059] The amount of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide added each accounts for 10% of the total weight of the seeds.
[0060] The binder is a 4.0% polyvinyl alcohol colloidal solution, and the mass ratio of the polyvinyl alcohol colloidal solution to the combined mass of micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide is 1:20.
[0061] The coating process of the above-mentioned coating material differs from that of Example 1 in that: Step 2, Super-acceleration Coating: Weigh out micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide according to the above raw material ratio, and prepare a binder. First, add wheat seeds and micron-sized iron powder to the super-acceleration coating device and mix them. Then add the binder. Set the operating conditions of the super-acceleration coating device to an acceleration of 80g, a frequency of 75Hz, and a running time of 5min. Then add nano-calcium phosphate and nano-magnesium hydroxide to the super-acceleration coating device. Similarly, set the operating conditions of the super-acceleration coating device to an acceleration of 80g and a frequency of 75Hz, and continue to run for 5min.
[0062] Example 4
[0063] This embodiment uses rice seeds.
[0064] A seed coating material for wheat and rice includes micron-sized iron powder, nano-sized calcium phosphate, nano-sized magnesium hydroxide, and a binder; The mass ratio of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is 4:1:1.
[0065] The amounts of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide added accounted for 12%, 3%, and 3% of the total seed weight, respectively.
[0066] The binder is a polyvinyl alcohol colloidal solution with a mass fraction of 8.0%, and the mass ratio of the polyvinyl alcohol colloidal solution to the combined mass of micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide is 1:31.
[0067] The coating process for the above-mentioned coating materials is as follows: Step 1, Seed pretreatment: Select plump rice seeds free from pests and diseases, remove shriveled, impurities and damaged seeds by winnowing and screening, and dry them in a well-ventilated environment at room temperature for later use. Step 2, Super-acceleration Coating: Weigh out micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide according to the above raw material ratio, and prepare a binder. First, add rice seeds and micron-sized iron powder to the super-acceleration coating device and mix them. Then add the binder. Set the operating conditions of the super-acceleration coating device to an acceleration of 60g, a frequency of 60Hz, and a running time of 5min to 10min. Then add nano-calcium phosphate and nano-magnesium hydroxide to the super-acceleration coating device. Similarly, set the operating conditions of the super-acceleration coating device to an acceleration of 60g and a frequency of 60Hz, and continue to run for 5min to 10min. Step 3, air drying: Dry the rice coated seeds under natural ventilation conditions.
[0068] Example 4 is the best embodiment of rice seed coating material.
[0069] Example 5
[0070] This embodiment uses rice seeds.
[0071] A seed coating material for wheat and rice includes micron-sized iron powder, nano-sized calcium phosphate, nano-sized magnesium hydroxide, and a binder; The mass ratio of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is 10:1:5.
[0072] The amounts of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide added account for 20%, 2%, and 10% of the total seed weight, respectively.
[0073] The binder is a 1.0% carboxymethyl cellulose colloidal solution, and the mass ratio of the carboxymethyl cellulose colloidal solution to the combined mass of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is 1:30.
[0074] The coating process of the above-mentioned coating material differs from that of Example 4 in that: Step 2, Super-acceleration Coating: Weigh out micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide according to the above raw material ratio, and prepare a binder. First, add rice seeds and micron-sized iron powder to the super-acceleration coating device and mix them. Then add the binder. Set the operating conditions of the super-acceleration coating device to an acceleration of 30g, a frequency of 55Hz, and a running time of 5min. Then add nano-calcium phosphate and nano-magnesium hydroxide to the super-acceleration coating device. Similarly, set the operating conditions of the super-acceleration coating device to an acceleration of 30g, a frequency of 55Hz, and a running time of 5min.
[0075] Example 6
[0076] This embodiment uses rice seeds.
[0077] A seed coating material for wheat and rice includes micron-sized iron powder, nano-sized calcium phosphate, nano-sized magnesium hydroxide, and a binder; The mass ratio of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is 10:6:5.
[0078] The amounts of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide added account for 10%, 6%, and 5% of the total seed weight, respectively.
[0079] The binder is a 5.0% carboxymethyl cellulose colloidal solution, and the mass ratio of the carboxymethyl cellulose colloidal solution to the combined mass of micronized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide is 1:25.
[0080] The coating process of the above-mentioned coating material differs from that of Example 4 in that: Step 2, Super-acceleration Coating: Weigh out micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide according to the above raw material ratio, and prepare a binder. First, add rice seeds and micron-sized iron powder to the super-acceleration coating device and mix them. Then add the binder. Set the operating conditions of the super-acceleration coating device to an acceleration of 80g, a frequency of 75Hz, and a running time of 10min. Then add nano-calcium phosphate and nano-magnesium hydroxide to the super-acceleration coating device. Similarly, set the operating conditions of the super-acceleration coating device to an acceleration of 80g, a frequency of 75Hz, and a running time of 10min.
[0081] Example 7
[0082] This embodiment uses rice seeds.
[0083] A seed coating material for wheat and rice includes micron-sized iron powder, nano-sized calcium phosphate, nano-sized magnesium hydroxide, and a binder; The mass ratio of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is 10:2:3.
[0084] The amounts of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide added account for 10%, 2%, and 3% of the total seed weight, respectively.
[0085] The binder is a hydroxypropyl methylcellulose colloidal solution with a mass fraction of 8.0%, and the mass ratio of the hydroxypropyl methylcellulose colloidal solution to the combined mass of micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide is 1:35.
[0086] The coating process of the above-mentioned coating material differs from that of Example 3 in that: Step 2, Super-acceleration Coating: Weigh out micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide according to the above raw material ratio, and prepare a binder. First, add rice seeds and micron-sized iron powder to the super-acceleration coating device and mix them. Then add the binder. Set the operating conditions of the super-acceleration coating device to an acceleration of 50g, a frequency of 65Hz, and an operating time of 8min. Then add nano-calcium phosphate and nano-magnesium hydroxide to the super-acceleration coating device. Similarly, set the operating conditions of the super-acceleration coating device to an acceleration of 50g, a frequency of 65Hz, and an operating time of 8min.
[0087] Example 8
[0088] This embodiment uses rice seeds.
[0089] A seed coating material for wheat and rice includes micron-sized iron powder, nano-sized calcium phosphate, nano-sized magnesium hydroxide, and a binder; The mass ratio of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is 6:2:1.
[0090] The amounts of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide added accounted for 18%, 6%, and 3% of the total seed weight, respectively.
[0091] The binder is a 15.0% hydroxypropyl methylcellulose colloidal solution, and the mass ratio of the hydroxypropyl methylcellulose colloidal solution to the combined mass of micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide is 1:45.
[0092] The coating process of the above-mentioned coating material differs from that of Example 3 in that: Step 2, Super-acceleration Coating: Weigh out micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide according to the above raw material ratio, and prepare a binder. First, add rice seeds and micron-sized iron powder to the super-acceleration coating device and mix them. Then add the binder. Set the operating conditions of the super-acceleration coating device to an acceleration of 70g, a frequency of 60Hz, and a running time of 6min. Then add nano-calcium phosphate and nano-magnesium hydroxide to the super-acceleration coating device. Similarly, set the operating conditions of the super-acceleration coating device to an acceleration of 70g, a frequency of 60Hz, and a running time of 6min.
[0093] Comparative Example 1
[0094] Wheat seeds, uncoated; Select plump wheat seeds free from pests and diseases, remove shriveled, impurities and damaged seeds by winnowing and screening, and dry them at room temperature under ventilated conditions for later use.
[0095] Comparative Example 2
[0096] Rice seeds, uncoated.
[0097] Select plump, disease-free rice seeds, remove shriveled, impurities and damaged seeds by winnowing and screening, and dry them at room temperature under ventilation for later use.
[0098] Comparative Example 3
[0099] This comparative example uses wheat seeds. The coating material uses only micron-sized iron powder and a binder (polyvinyl alcohol colloidal solution).
[0100] A seed coating material for wheat and rice includes micron-sized iron powder and a binder, wherein the micron-sized iron powder has a particle size of 80 μm.
[0101] The amount of micron-sized iron powder added accounts for 10% of the total weight of the seeds.
[0102] The binder is a 6.0% polyvinyl alcohol colloidal solution, and the mass ratio of the polyvinyl alcohol colloidal solution to the micron-sized iron powder is 1:30.
[0103] The coating process for the above coating materials: Step 1, Seed pretreatment: Select plump wheat seeds free from pests and diseases, remove shriveled, impurities and damaged seeds by winnowing and screening, and dry them in a well-ventilated environment at room temperature for later use. Step 2, Super-acceleration coating: Weigh the micronized iron powder according to the above raw material ratio and prepare the binder. First, add wheat seeds and micronized iron powder to the super-acceleration coating device and mix them. Then add the binder. Set the operating conditions of the super-acceleration coating device to an acceleration of 50g, a frequency of 60Hz, and an operating time of 5min to 10min. Step 3, air drying: Dry the wheat coated seeds under natural ventilation conditions.
[0104] Comparative Example 4
[0105] This comparative example uses wheat seeds. The coating material used is only nano-calcium phosphate and binder (carboxymethyl cellulose colloidal solution).
[0106] A seed coating material for wheat and rice includes nano-calcium phosphate and a binder, wherein the nano-calcium phosphate has a particle size of 90 nm.
[0107] The binder is a 1.5% carboxymethyl cellulose colloidal solution, with a mass ratio of 1:1 between the carboxymethyl cellulose colloidal solution and the nano-calcium phosphate.
[0108] The coating process for the above coating materials: Step 1, Seed pretreatment: Select plump wheat seeds free from pests and diseases, remove shriveled, impurities and damaged seeds by winnowing and screening, and dry them in a well-ventilated environment at room temperature for later use. Step 2, Super-acceleration coating: Weigh the nano-calcium phosphate according to the above raw material ratio and prepare the binder. First, add wheat seeds and nano-calcium phosphate into the super-acceleration coating device and mix them. Then add the binder. Set the operating conditions of the super-acceleration coating device to an acceleration of 50g, a frequency of 60Hz, and an operating time of 5min to 10min. Step 3, air drying: Dry the wheat coated seeds under natural ventilation conditions.
[0109] Comparative Example 5
[0110] This comparative example uses wheat seeds. The coating material used is only nano-magnesium hydroxide and a binder (hydroxypropyl methylcellulose colloidal solution).
[0111] A seed coating material for wheat and rice includes nano-magnesium hydroxide and a binder, wherein the nano-magnesium hydroxide has a particle size of 30 nm.
[0112] The binder is a 10.0% hydroxypropyl methylcellulose colloidal solution, and the mass ratio of the hydroxypropyl methylcellulose colloidal solution to nano-magnesium hydroxide is 1:20.
[0113] The coating process for the above coating materials: Step 1, Seed pretreatment: Select plump wheat seeds free from pests and diseases, remove shriveled, impurities and damaged seeds by winnowing and screening, and dry them in a well-ventilated environment at room temperature for later use. Step 2, Super-acceleration coating: Weigh nano-magnesium hydroxide according to the above raw material ratio and prepare binder. First, add wheat seeds and nano-magnesium hydroxide into the super-acceleration coating device and mix them. Then add binder. Set the operating conditions of the super-acceleration coating device to an acceleration of 50g, a frequency of 60Hz, and an operating time of 5min to 10min. Step 3, air drying: Dry the wheat coated seeds under natural ventilation conditions.
[0114] Comparative Example 6
[0115] The difference from Comparative Example 3 is that this comparative example uses rice seeds.
[0116] Comparative Example 7
[0117] The difference from Comparative Example 4 is that this comparative example uses rice seeds.
[0118] Comparative Example 8
[0119] The difference from Comparative Example 5 is that this comparative example uses rice seeds.
[0120] The wheat coated seeds obtained in Example 1, Comparative Example 1, Comparative Example 3, Comparative Example 4, and Comparative Example 5 of this invention are as follows: Figure 1As shown.
[0121] The rice coated seeds obtained in Examples 4, 2, 6, 7 and 8 of this invention are as follows: Figure 2 As shown.
[0122] In this invention, the superacceleration coating device is specifically an acoustic resonance meter.
[0123] Experiment and results: I. Wheat and rice coated seeds obtained in Examples 1-8 and Comparative Examples 1-8 were selected for compressive strength, disintegration rate, and dust shedding rate tests. The test results are shown in Table 1. Table 1 Seed performance tests of Examples 1-8 and Comparative Examples 1-8
[0124] Results analysis: (1) Seed compressive strength: The compressive strength of the wheat-coated seeds in Examples 1-3 was superior to that of the untreated wheat seeds in Comparative Example 1 (34.839 kgF / mm²), and also superior to that of the wheat-coated seeds provided in Comparative Examples 3-5.
[0125] The compressive strength of the rice coated seeds in Examples 4-8 was superior to that of the untreated rice seeds in Comparative Example 2 (14.554 kgF / mm²), and also superior to that of the rice coated seeds provided in Comparative Examples 6-8.
[0126] It is evident that the coating material for wheat and rice seeds uses a mixture of three components: micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide. This improves the compressive strength of the seeds, enabling them to meet the requirements of high-speed mechanized sowing and significantly reducing the rates of missed sowing and reseeding.
[0127] (2) Disintegration rate: The disintegration rate of the coated seeds in Comparative Examples 3-8 was ≤50% or ≥70%, while the disintegration rate of the coated seeds in Examples 1 to 8 was in the range of 50% to 70%. This moderate disintegration rate can ensure that the seeds can quickly release functional components after sowing, while avoiding functional failure or structural damage caused by excessive disintegration. This indicates that the coated seeds of the present invention have better balance performance in terms of disintegration rate.
[0128] (3) pH value: The pH values of Examples 1 to 8 of the present invention are alkaline. The coated seeds of the present invention can provide an alkaline environment, which creates a favorable environment for the adsorption of mineralized heavy metal ions.
[0129] (3) Dust shedding rate: The shedding rate of the coated seeds in Examples 1 to 8 of the present invention is ≤0.20%. The low dust shedding rate of the coated seeds of the present invention improves the stability and reliability of the seeds in mechanized operations.
[0130] II. Testing of Seed Germination and Early Seedling Growth
[0131] (1) Taking Example 1 and Comparative Example 1 as examples, according to the wheat seed section of GBT 3543.4-2025 "Specifications for Crop Seed Inspection Part 4: Germination Test of Sowing Quality", 15g of wheat seeds were placed directly on the germination tray in a constant temperature incubator, with moist loose paper as a substrate, and cultivated in a constant temperature incubator at 20℃. The germination and early seedling growth of wheat seeds in Example 1 and Comparative Example 1 were detected, and the sprout length and root length on the 4th and 8th days were recorded. The results are shown in Table 2. Figures 3 to 6 As shown.
[0132] Table 2 Comparison of wheat seedling development
[0133] On day 4, the root length of the seedlings was: Example 1 (59.23 mm) > Comparative Example 1 (40.81 mm), and the shoot length was: Example 1 (78.81 mm) > Comparative Example 1 (72.95 mm).
[0134] On day 8, the root length of the seedlings was: Example 1 (108.22 mm) > Comparative Example 1 (79.74 mm), and the shoot length was: Example 1 (138.83 mm) > Comparative Example 1 (109.64 mm).
[0135] According to Table 2, Figures 3 to 6 It can be seen that the coating material of the present invention significantly promotes the early root and shoot growth of wheat seeds.
[0136] (2) Taking Example 4 and Comparative Example 2 as examples, according to the rice seed section of GB / T 3543.4-2025 "Specifications for Crop Seed Inspection Part 4: Germination Test for Sowing Quality", 13g of rice seeds were placed directly on the germination tray in a constant temperature incubator, with moist, loose paper as a liner, and cultivated in a constant temperature incubator at 25℃. The germination and early seedling growth of the rice seeds in Comparative Example 4 were measured. The root length and shoot length were recorded after 5 days and 14 days of cultivation in the constant temperature incubator, as shown in Table 3. Figures 7 to 10 As shown.
[0137] Uncoated rice seeds germinate slowly in the early stages of germination, starting to germinate on the 4th day, while the rice seeds obtained in Example 4 germinate rapidly, starting to germinate on the 2nd day.
[0138] On day 5, the root length of the seedlings was 54.87 mm in Example 4, which was greater than that in Comparative Example 2 (27.66 mm). The shoot length was 47.19 mm in Example 4, which was greater than that in Comparative Example 2 (11.26 mm). The early root and shoot growth were significantly promoted. On day 14, the root length of the seedlings was: Example 4 (120.26 mm) > Comparative Example 2 (112.65 mm), and the shoot length was: Mixed component (88.82 mm) > Comparative Example 2 (75.36 mm).
[0139] Through Table 3, Figures 7 to 10 It is evident that the coating material of the present invention has a significant promoting effect on rice seed germination and seedling development.
[0140] Table 3 Comparison of rice seedling development
[0141] Test results on seed germination and early seedling growth show that the coating material of this invention can significantly improve the germination rate of wheat and rice seeds and the growth performance of seedlings. The three components of the coating material—micronized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide—work synergistically to provide necessary physical protection for the seeds. The slow-release active ingredients of Fe, P, and Mg elements promote early seed development, resulting in seedling root and shoot length and seedling vigor superior to uncoated seeds.
[0142] III. Isothermal Adsorption Experiments of Micron-sized Iron Powder, Nano-sized Calcium Phosphate, and Nano-sized Magnesium Hydroxide on Lead, Cadmium, and Arsenic Heavy Metal Ions
[0143] The lead nitrate (Pb(NO3)2), cadmium nitrate tetrahydrate (Cd(NO3)2·4H2O), and disodium arsenate heptahydrate (Na2HAsO4·7H2O) used in the adsorption experiment of this invention are all derived from Aladdin reagents.
[0144] (1) Isothermal adsorption test of lead, cadmium and arsenic heavy metal ions by micron iron powder
[0145] Micronized iron powder was added to Pb² at a dosage of 1 g / L. + Pb(NO3)2 aqueous solution with a concentration of 200-800 mg / L, Cd² + An aqueous solution of Cd(NO3)2·4H2O with a concentration of 100-600 mg / L, and AsO4³ - The Pb²⁺ ions were dissolved in an aqueous solution of Na₂HAsO₄·7H₂O with a concentration of 50-300 mg / L and shaken at 40 rpm and 30 °C in a constant temperature water bath until adsorption equilibrium was reached. The solution was then filtered through a 0.22 μm filter membrane, and the Pb²⁺ concentration in the filtrate was measured using an inductively coupled plasma optical emission spectrometer (ICP-OES).+ Cd² + AsO4³ - The concentration, such as Figure 11 As shown, the adsorption amount q at equilibrium is calculated according to formula (1). e To obtain micron-sized iron powder for Pb² + Cd² + AsO4³ - Maximum adsorption capacity: Qt(Pb²) + ) Max =328.91mg / g, Q t (Cd²) + ) Max =157.35mg / g, Q t (AsO4³) - ) Max =77.86mg / g.
[0146] (2) Isothermal adsorption test of lead, cadmium and arsenic heavy metal ions by nano-calcium phosphate
[0147] Nano-calcium phosphate was added to Pb² at a dosage of 1 g / L. + Pb(NO3)2 aqueous solution with a concentration of 600-1500 mg / L; Cd² + Cd(NO3)2·4H2O aqueous solution with a concentration of 100-700 mg / L; AsO4³ - Aqueous solutions of Na₂HAsO₄·7H₂O with concentrations of 30-300 mg / L were prepared and shaken at 40 rpm and 30 °C using a constant temperature water bath shaker until adsorption equilibrium was reached. The solutions were then filtered through a 0.22 μm filter membrane, and the Pb² concentration in the filtrate was measured using an inductively coupled plasma optical emission spectrometer (ICP-OES). + Cd² + AsO4³ - The concentration, such as Figure 12 As shown, the adsorption amount q at equilibrium is calculated according to formula (1). e To obtain nano-calcium phosphate for Pb² + Cd² + AsO4³ - Maximum adsorption capacity: Q t (Pb²) + ) Max =631.1mg / g, Q t (Cd²) + ) Max =153.08mg / g, Q t (AsO4³) - ) Max =36.05mg / g.
[0148] (3) Isothermal adsorption test of lead, cadmium and arsenic heavy metal ions by nano magnesium hydroxide
[0149] Nano-magnesium hydroxide was added to Pb² at a dosage of 1 g / L. + Aqueous solutions of Pb(NO3)2 with a concentration of 200-800 mg / L; Cd² + Cd(NO3)2·4H2O aqueous solution with a concentration of 100-600 mg / L; AsO4³ - Na₂HAsO₄·7H₂O aqueous solutions with concentrations of 50-300 mg / L were prepared and shaken at 40 rpm and 30 °C using a constant temperature water bath shaker until adsorption equilibrium was reached. The solutions were then filtered through a 0.22 μm filter membrane, and the Pb²⁺ concentration in the filtrate was measured using an inductively coupled plasma optical emission spectrometer (ICP-OES). + Cd² + AsO4³ - The concentration, such as Figure 13 As shown, the adsorption amount q at equilibrium is calculated according to formula (1). e To obtain nano-magnesium hydroxide for Pb² + Cd² + AsO4³ - Maximum adsorption capacity: Q t (Pb²) + ) Max =286.5mg / g, Q t (Cd²) + ) Max =173.52mg / g, Q t (AsO4³) - ) Max =58.95mg / g.
[0150] (1)
[0151] Where, q e The adsorption amount at equilibrium is expressed in mg / g; CO refers to the amount of Pb² in the solution. + Cd² + or AsO4³ - Initial concentration, mg / L; C e Pb² in solution at adsorption equilibrium + Cd² + or AsO4³ - The concentration is mg / L; V refers to the solution volume, mL; m is the mass of micron-sized iron powder, nano-sized calcium phosphate, or nano-sized magnesium hydroxide added, g.
[0152] Comparative analysis of experimental results on the adsorption of lead, cadmium, and arsenic heavy metal ions by micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide showed that micron-sized iron powder effectively removed AsO4³⁺ ions. - The most powerful, nano-calcium phosphate removes Pb² + The most powerful nano-magnesium hydroxide for removing Cd² + The seed coating material of this invention exhibits the strongest adsorption capacity. The mixing of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is achieved through the addition of a suitable binder, without involving material modification. Therefore, in practical applications, this mixing method not only simplifies the process but also effectively preserves the original adsorption properties of each component. Experimental data shows that different materials exhibit significant differences in their selective adsorption capacity for heavy metal ions. The synergistic effect of the three materials further enhances the adsorption effect on lead, cadmium, and arsenic heavy metals in soil, especially demonstrating strong adaptability in complex polluted environments. This characteristic allows coated seeds to maintain a high germination rate and growth potential in soils contaminated with heavy metals, providing a strong guarantee for the safe production of wheat and rice.
[0153] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A seed coating material for wheat and rice, characterized in that, It includes micron-sized iron powder, nano-sized calcium phosphate, nano-sized magnesium hydroxide, and a binder; the amount of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide added accounts for 10%–20%, 2%–10%, and 3%–10% of the total weight of the seeds, respectively; The adhesive is at least one of polyvinyl alcohol colloidal solution, carboxymethyl cellulose colloidal solution, and hydroxypropyl methyl cellulose colloidal solution; The mass ratio of the binder to the mass of micronized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide is 1:20-1:
50.
2. The seed coating material for wheat and rice as described in claim 1, characterized in that, The amount of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide added accounts for 10%, 3%, and 3% of the total weight of the seeds, respectively; the binder is a polyvinyl alcohol colloidal solution with a mass fraction of 8.0%, and the mass ratio of the polyvinyl alcohol colloidal solution to the mass of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is 1:
32.
3. The seed coating material for wheat and rice as described in claim 1, characterized in that, The amount of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide added accounts for 12%, 3%, and 3% of the total weight of the seeds, respectively; the binder is a polyvinyl alcohol colloidal solution with a mass fraction of 8.0%, and the mass ratio of the polyvinyl alcohol colloidal solution to the mass of micron-sized iron powder, nano-sized calcium phosphate, and nano-sized magnesium hydroxide is 1:
31.
4. The seed coating material for wheat and rice as described in claim 1, characterized in that, The mass ratio of the micron-sized iron powder, nano-sized calcium phosphate and nano-sized magnesium hydroxide is (1-10):(1-6):(1-5).
5. The seed coating material for wheat and rice as described in claim 4, characterized in that, The mass ratio of the micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide is 10:3:
3.
6. The seed coating material for wheat and rice as described in claim 4, characterized in that, The mass ratio of the micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide is 4:1:
1.
7. The seed coating material for wheat and rice as described in claim 1, characterized in that, The polyvinyl alcohol colloidal solution has a mass fraction of 4.0% to 10.0%; the carboxymethyl cellulose colloidal solution has a mass fraction of 1.0% to 5.0%; and the hydroxypropyl methyl cellulose colloidal solution has a mass fraction of 8.0% to 15.0%.
8. The coating process for wheat and rice seed coating materials as described in any one of claims 1-7, characterized in that, Specifically, the following steps are included: Step 1, Seed pretreatment: Select plump wheat or rice seeds free from pests and diseases, remove shriveled, impurities and damaged seeds by winnowing and screening, and dry them at room temperature under ventilation for later use. Step 2, Super-acceleration Coating: Weigh out micron-sized iron powder, nano-calcium phosphate, and nano-magnesium hydroxide according to the above raw material ratio, and prepare a binder. First, add wheat or rice seeds and micron-sized iron powder to the super-acceleration coating device and mix them. Then add the binder. Set the operating conditions of the super-acceleration coating device to an acceleration of 30g-80g, a frequency of 55Hz-75Hz, and a running time of 5min-10min. Then add nano-calcium phosphate and nano-magnesium hydroxide to the super-acceleration coating device. Similarly, set the operating conditions of the super-acceleration coating device to an acceleration of 30g-80g and a frequency of 55Hz-75Hz, and continue running for 5min-10min. Step 3, air drying: Dry the wheat and rice coated seeds under natural ventilation conditions.
Citation Information
Patent Citations
Pelletized barley seeds as well as preparation method and application thereof
CN120959247A
Rice direct seeding seed coating method taking iron powder as main raw material
CN117561836A
Rice seed coating agent based on halloysite nanotubes as well as preparation method and application of rice seed coating agent
CN119547778A
Pretreatment method for iron powder coating breeding
CN121153411A
Coating agent for paddy seed, and paddy seed coated therewith
JP2012224566A
Cited By
Water-retaining gel, traditional chinese medicine seed coating agent, preparation method thereof and application in promoting traditional chinese medicine seed germination and drought resistance
CN122234474A